Reversal of increased mammary tumorigenesis by valproic acid and hydralazine in offspring of dams fed high fat diet during pregnancy - F. de Oliveira Andrade; N. M. Nguyen; A. Warri; L. Hilakivi-Clarke (Nature Publishing Group (NPG), 2025)
Maternal or paternal high fat (HF) diet can modify the epigenome in germ cells and fetal somatic cells leading to an increased susceptibility among female offspring of multiple generations to develop breast cancer. We determined if combined treatment with broad spectrum DNA methyltransferase (DNMT) inhibitor hydralazine and histone deacetylase (HDAC) inhibitor valproic acid (VPA) will reverse this increased risk. C57BL/6 mouse dams were fed either a corn oil-based HF or control diet during pregnancy. Starting at age 7 weeks, female offspring were administered 3 doses of 7,12-dimethylbenz[a]anthracene (DMBA) to initiate mammary cancer. After last dose, offspring started receiving VPA/hydralazine administered via drinking water: no adverse health effects were detected. VPA/hydralazine reduced mammary tumor multiplicity and lengthened tumor latency in HF offspring when compared with non-treated HF offspring. The drug combination inhibited DNMT3a protein levels and increased expression of the tumor suppressor gene Cdkn2a/p16 in mammary tumors of HF offspring. In control mice not exposed to HF diet in utero, VPA/hydralazine increased mammary tumor incidence and burden, and elevated expression of the unfolded protein response and autophagy genes, including HIF-1α, NFkB, PERK, and SQSTM1/p62. Expression of these genes was already upregulated in HF offspring prior to VPA/hydralazine treatment. These findings suggest that breast cancer prevention strategies with HDAC/DNMT inhibitors need to be individually tailored.